A pilot study of universities' willingness to solicit whistleblowers for participation in a study. Issue 4 (1st October 2016) - Byrn, Melissa J.; Redman, Barbara K.; Merz, Jon F.
ABSTRACT: Background : It has been more than two decades since the only interview study of whistleblowers in academic research. There remains a need to appreciate whistleblower experience, role in scientific integrity, and whether policies provide adequate protection.Methods : We contacted the institutional official for research, the institutional review board (IRB) director, and the Institutional Animal Care and Use Committee (IACUC) director from a random sample of 25 of the highest 200 NIH funded institutions. We assessed the willingness of respondents to send a hypothetical solicitation letter to whistleblowers who had lodged complaints related to research.Results : The response rate was 41%. Despite a willingness to distribute a solicitation letter (68% respondents), most wanted further institutional approval before sending it (76%).Conclusion : Data from this pilot study suggest substantial obstacles to obtaining access to whistleblowers by way of anonymous solicitation letters distributed by institutions.